PENDEKATAN META ANALISIS : FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEPALA SEKOLAH - Ariyani, Retno; Paramitra, Monica Dewi; Bektiarso, Singgih; Budiarso, Aris Singgih; Siswati, Bea Hana (Jurnal Inovasi dan Teknologi Pendidikan, 2026)
Principal performance is a key factor in determining the success of educational management and quality improvement in educational institutions. This study aims to identify and analyze the factors affecting principal performance through a meta-analysis approach. The method employed is a qualitative approach with meta-analysis techniques applied to 10 national and international journal publications published between 2020-2025. The analysis identified 8 main factors affecting principal performance: (1) discipline and work ethic (2) creativity and innovation in leadership; (3) communication competence and interpersonal relations; (4) supervision system and academic coaching; (5) organizational culture and work atmosphere; (6) motivation and internal drive; (7) leadership style and approach; and (8) development of professional capacity of teaching staff. The findings indicate that creativity-innovation and work motivation have the most substantial direct effects on principal performance. These factors interact synergistically and demonstrate consistency across various educational contexts, although their implementation requires adaptation according to the socio-cultural and geographical conditions of each region. This research provides theoretical contributions to understanding the complexity of factors affecting principal performance and offers practical implications for developing educational leadership training programs.